Basic Sanitation in Residential Areas of Wakal Village, Leihitu Subdistrict, Central Maluku Regency - Mewar, liza; Pinoa, Wiclif Sephnath; Tetelepta, Edward Gland (Universitas Pattimura, 2024)
Basic sanitation is an effort to provide minimum facilities in accordance with health standards, such as TPS, SPAL, healthy latrines, and clean water, in order to prevent humans from coming into direct contact with dirt and aiming to promote healthy living. Both community and family based, basic sanitation facilities are very important in supports health. Sanitation is a process carried out in monitoring environmental factors whose role can be detrimental to health. Sanitation is a process carried out in monitoring environmental factors with a role that can disrupt health. This is a descriptive survey that is sent to households which is used to provide information not only about the family but also information about the environment and the house. The research will be carried out in Negeri Wakal, Leihitu District. The results of this research were conducted to determine community behavior patterns in managing basic residential sanitation which was studied in terms of clean water facilities, latrines, waste facilities and waste water disposal channels (SPAL). In the residential area of Wakal Village, Leihitu sub-district. The number studied was 30 heads of families who were taken randomly